The Key Role of Social Movements in Protecting the Health of People and the Planet; Comment on "Ensuring Global Health Equity in a Post-pandemic Economy" - Chiara Bodini (Kerman University of Medical Sciences, 2023)
In his recent article, titled "Ensuring Global Health Equity in a Post-pandemic Economy," Ronald Labonté addresses a key challenge the world is facing, trying to 'build back' after the global crisis related to the COVID-19 pandemic. He explores and critically examines different policy options, from a more inclusive 'stakeholder model' of capitalism, to a greater role of states in shaping markets and investing in the protection of health and the environment, to more radical options that propose to reframe the capitalist mantra of growth and look at different ways to value and center our societies around what really matters most to protect life. Social movements are key players in such transformation, however the political space they move in is progressively shrinking.